PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DI TOKO LISA JAYA BENGKULU - Subandrio, Subandrio; Amarta, Elsa (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine the effect of price and service quality on repurchase interest at Lisa Jaya Bengkulu, either partially or simultaneously. There are several factors that will be discussed in this study, including Price and Quality of Service. The object of this research is 60 customers who shop at Lisa Jaya Bengkulu shop.In this study the authors used descriptive research methods with quantitative data analysis. The data collection in this study is by means of observation, distributing questionnaires or questionnaires. There are several data analysis techniques used in this research, including instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing.Based on the results of multiple linear regression, the regression equation is Y = 2.696 + 0.316 (X1) + 0.480 (X2). The results of the t hypothesis test show that the variable price (X1), shows t count of 2.266 > t table 2.00247 with a significant level of 0.027 < of 0.050. Service Quality Variable (X2), shows t count of 4.525 > t table 2.00247 with a significant level of 0.000 < of 0.050. While the results of the F hypothesis test show that the significance value of F is 0.000 < 0.050 and Fcount> Ftable, 24.033 > 3.166. So it can be concluded that price and service quality have a positive and significant effect on repurchase interest at Lisa Jaya Bengkulu shop.Â Keywords: Price, Quality Of Service And Interest In Repurchasing